Dampak Sistem Evaluasi Pelanggan kepada Psikologis Pengemudi Ojek Online - Yuriadi; Ayu Aisyah Putri Dyah Pratiwi; Firawati Marlinda; Nafisah Amatullah (CV. Era Digital Nusantara, 2026)
This study aims to examine the customer evaluation system, its resulting effects, the psychological reactions of online motorcycle taxi drivers, and the methods used to cope with the system's impact. A qualitative method was employed to explore the drivers' experiences with the customer evaluation system. Data analysis involved data reduction, data presentation, and drawing conclusions based on themes identified during interviews. The results indicate that the customer evaluation system affects both the operational and psychological aspects of the drivers. Operationally, low ratings and negative reviews lead to poorer account performance, fewer orders, and reduced income. Psychologically, negative evaluations cause disappointment, frustration, and discomfort, particularly when the feedback is perceived as inconsistent with the actual situation. However, most drivers do not suffer prolonged emotional distress, as they are able to view these evaluations as an inherent risk of the job. Drivers demonstrate adaptability by accepting the situation, engaging in self-evaluation, improving service quality, managing their emotions, and addressing customer complaints responsibly. The customer evaluation system needs to be made fairer and more transparent.